Preliminary Report on the Excavations at Khairkhan-1 Cave in Zavkhan Aimag, Western Mongolia (Studia Archaeologica, 2025)
In the western part of Mongolia stratified Paleolithic sites are still unknown. In the territory of Zavkhan aimag is located the Ikh-Khairkhan limestone massif. Here in 2023 the joint Russian-Mongolian archaeological expedition excavated the Khairkhan-1 cave on the area of 2 sq. ms. The depth of excavated sediments was 2 ms. Four main lithological layers were identified. Archaeological assemblages are contained in layers 1-3. The most abundant assemblage of layer 3 contains flake-based industry characterised by an overwhelming predominance of small flakes. The faunal assemblage of Layer 3 includes fragments of ostrich eggshells, bear, hare and horse bones. A rhinoceros tooth was found in Layer 3.1. In layer 4, bones of a pika, bear, and a fragment of an antelope jaw were found. Most likely, the formation of the upper part of the section up to layer 3.1. can be attributed to the early stages of the Holocene - final Pleistocene. Layers 3.1. and below, based on their faunal composition and sediment features, can be dated to the period of the last glacial maximum associated with climate aridization and increased aeolian activity. The collections obtained during the cave excavations have an archaic appearance and have no direct archaeological analogues in the Holocene complexes of Mongolia.